Implementasi Pembelajaran Berbasis Experiential Learning untuk Mengembangkan Kemampuan Berpikir Kritis Pemuda Rentan di PSBR Taruna Jaya 1 - Avia Destimianti; Kayla Dea Aosa; Tiffany Cindy Adristi (Abdimas Indonesian Journal, 2026)
Critical thinking is an essential twenty-first-century competency, particularly for vulnerable youth facing social, economic, and educational challenges. This study examines the implementation of Experiential Learning in developing critical thinking skills among vulnerable youth at PSBR Taruna Jaya 1. A descriptive quantitative approach supported by qualitative observations was employed. Learning outcomes were assessed using pre-tests and post-tests across five learning sessions, while facilitator observations captured participants' engagement and behavioral changes. The results showed that three of the five sessions produced statistically significant improvements in participants' post-test scores, while the remaining sessions demonstrated positive but non-significant gains. Observations also revealed increased participation, confidence in expressing ideas, collaboration, and reflective thinking throughout the program. These findings indicate that Experiential Learning is a promising approach for developing critical thinking skills among vulnerable youth. Future implementations should strengthen facilitation strategies, refine learning activities, and enhance evaluation instruments to achieve more consistent learning outcomes.